Genomic fingerprints produced by PCR with consensus tRNA gene primers. - Welsh, J (1991)
The polymerase chain reaction using only a single 'consensus' tRNA gene primer, or a pair of primers facing outward from tRNA genes, amplifies a set of DNA fragments in bacterial, plant and animal genomic DNAs. Presumably, these PCR fingerprints are mainly derived from the regions between closely linked tRNA genes. The pattern of the PCR products is determined by which genomes and which primer(s) are used. Genomic fingerprints are largely conserved within a species and, in bacteria, most products in the fingerprint are conserved between closely related species. Thus, PCR with tRNA gene consensus primers helps to identify species and genera.